Glycerophosphoinositol modulates FGA and NOTCH3 in exercise-induced muscle adaptation and colon cancer progression - Luo, Hongbiao; Luo, Wei; Ding, Ning; Zhu, Huimin; Lai, Jiahui; Tang, Qingzhu; He, Yongheng (Frontiers in Pharmacology, 2024)
Objectives: Fibroleukin (FGA) and NOTCH3 are vital in both exercise-induced muscle adaptation and colon adenocarcinoma (COAD) progression. This study aims to elucidate the roles of FGA and NOTCH3 in phenotypic variations of striated muscle induced by exercise and in COAD development. Additionally, it seeks to evaluate the prognostic significance of these proteins. Methods: Gene Set Variation Analysis (GSVA) and protein-protein interaction (PPI) network analysis were employed to identify differentially expressed genes (DEGs). Molecular docking studies were conducted to assess the binding affinities of 39 compounds to the NOTCH3 protein. In vitro assays, including mobileular viability, gene expression, and apoptosis assays, were performed to evaluate the effects of glycerophosphoinositol on FGA and NOTCH3 expression. Additionally, copy number variation (CNV), methylation status, and survival analyses were conducted across multiple cancers types. Results: The NOTCH signaling pathway was consistently upregulated in exercise-induced muscle samples. High NOTCH3 expression was associated with poor prognosis in COAD, extracellular matrix organization, immune infiltration, and activation of the PI3K-Akt pathway. Molecular docking identified gamma-Glu-Trp, gamma-Glutamyltyrosine, and 17-Deoxycortisol as strong binders to NOTCH3. Glycerophosphoinositol treatment modulated FGA and NOTCH3 expression, influencing cell proliferation and apoptosis. CNV and methylation analyses revealed specific changes in FGA and NOTCH3 across 20 cancers types. Survival analyses showed strong associations between FGA/NOTCH3 expression and survival metrics, with negative correlations for FGA and positive correlations for NOTCH3. Conclusion: FGA and NOTCH3 play significant roles in exercise-induced muscle adaptation and colon cancer progression. The expression profiles and interactions of these proteins provide promising prognostic markers and therapeutic targets. These findings offer valuable insights into the post-translational modifications (PTMs) in human cancer, highlighting novel pharmacological and therapeutic opportunities.